Clinical and laboratory importance of detecting Helicobacter pylori coccoid forms for the selection of treatment - Gladyshev, Nikita; Taame, Maria; Kravtsov, Viacheslav (Gastroenterology Review/Przegląd Gastroenterologiczny, 2020)
Helicobacter pylori grows and multiplies in the gastrointestinal tract (GIT) in about half of the world’s population. The prevalence of diseases associated with this bacterium is steadily increasing, which makes it necessary to search for optimal therapy aimed at eradication of this bacterium. Such diseases, for example, include gastric ulcer (GU) and chronic gastritis (CG). Unfortunately, modern possibilities for eradication therapy do not always make it possible to cure patients, and relapses often occur if it is cured. Nowadays, a particular topical issue has arisen, which concerns the resistance of Helicobacter pylori to therapies, because the effectiveness of medication used in clinics decreases every year. One of the mechanisms favouring tolerance to antibiotics is the transformation into a different morphological form – coccoid. This form of the bacterium was discovered quite a long time ago. Nevertheless, the question of its importance in clinical practice remains open to this day. Modern studies are aimed at understanding the role of coccoid forms of H. pylori in the survival of the population of these bacteria and at clarifying their role in the pathogenesis of gastrointestinal diseases. It is not known whether it is necessary to evaluate the contamination of a given morphological form of a bacterium of the gastric mucosa in clinical practice and its influence on the development of diseases etc. This article presents an overview and analysis of modern ideas about H. pylori coccoid forms and answers to the main questions posed in the last 10 years regarding the study of coccoid forms. Additionally, our results present a comparison of expression of virulence factors in coccoid and spiral forms of H. pylori.